Matoa Leaf Serum (Pometia pinnata Forst) : Physical Characteristics and Antioxidant Activity - Khairunnisa, Amalia (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Matoa Leaf (Pometia pinnata Forst) has antioxidant activity that inhibits free radicals. This research aims to determine the physical characteristic and antioxidant activity of facial serum Matoa leaves (P. pinnata Forst.) with concentrations of the ethanol extract F1 (1%), F2 (3%), and F3 (5%). The physical characteristics tested included organoleptic, homogeneity, pH, viscosity, spreadability, and adhesivity. Antioxidant activity was determined by the DPPH method. The organoleptic results showed that the serum had a yellowish-brown to greenish-brown color, a distinctive aroma of extract, a slightly viscous liquid, and homogeneity. pH test results in F1, F2, and F3 were 6.93±0.02, 5.66±0.02, and 5.05±0.01. Viscosity test results in F1, F2, and F3 were 2983.3±76.3 cP, 3200±50 cP, and 3950.0±50.0 cP. Spreadability test results in F1, F2, and F3 were 5.33±0.05 cm, 5.06±0.05 cm, and 5.03±0.05 cm. Adhesivity test results in F1, F2, and F3 were 1.3±0.04 seconds, 1.89±0.07 seconds, and 2.43±0.09 seconds. Antioxidant activity values in F1, F2, and F3 were 206,445±2,900 ppm (very weak), 149,464±4,025 ppm (moderate), and 49,204±0.383 ppm (very strong). This research concludes that increasing the concentration of the extract increases color and aroma intensity, viscosity, and adhesivity, and decreases the pH value, spreadability, and IC50 value of facial serum.